STUDY OF PENDANTS MADE OF RESIN PRODUCED BY THE ART FOLK VILLAGE INSTITUTION - Israwati Hamsar; Ismayanti Hamsar; Hasnawati Hasnawati; Irfan Irfan (Universitas Negeri Makassar, 2022)
The background of the problem in this study is the lack of craftsmen in making pendants made from resin, this becomes a problem because this pendant is quite a in demand to be used as souvenirs at weddings, by doing this research the public can be invited directly to see the process of making this pendant. , as an effort to find people who are interested in becoming a pendant craftsman made of resin. This study aims to describe the process of making pendants made from. The type of research is survey research with a descriptive qualitative data analysis technique. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques in the form of data collection, data reduction, data presentation, and data verification. The results showed 1) the pendant manufacturing process consisted of several stages, first: preparation of tools and materials, second: selection of raw materials, third: assembling the main material with additional materials such as resins, catalysts, and dyes, fourth: printing process, fifth: drying process, sixth: finishing includes sanding and brassoing.